Analysis of Transients in Overhead Telecommunication Subscriber Line Due to Nearby Lightning Return Stroke - Sorwar, M.G.; Ahmad, Hussein; Ali, M.M. (1998)
A simple analysis of induced transients in an overhead telecommunication subscriber line due to nearby lightning return stroke to the ground is done considering a simple triangular pulse current as channel current. The field-transmission line coupling model is adopted from Agrawal et al. (1980). Results show that the front return stroke produces higher peak value of transients in comparison with the side return stroke, on the other hand side return stroke produces higher values of front steepness. The numerical results have a good agreement with the experimental data